ALCOHOLIC EXTRACTS OF Vitex agnus-castus AND Populus euphratica IN CONTROLLING Hyalomma anatolicum PARASITIZING LIVESTOCK (Nativa, 2023)
ABSTRACT: The study was conducted from the beginning of April 2022 to the end of December 2022 in Kirkuk governorate, Al-Huweija district. The study examined the alcoholic extracts efficacy of Vitex agnus-castus and Populus euphratica in controlling the hard tick Hyalomma anatolicum using the dipping method. All treated larvae died within 48 hours of treatment. The alcoholic extract of P. euphratica was more effective in killing tick nymphs at a 90 mg mL-1 concentration during the nymphal stage. The mortality rate was 100%. The lowest mortality rate was 67.7% at a concentration of 30 mg mL-1 after 96 hours of treatment. As for the V. agnus-castus alcoholic extract, the highest mortality rate at a concentration of 90 mg mL-1 was 93.33%, while the lowest was 66.66% after 96 hours of treatment. The alcoholic extract of the combination achieved a mortality rate of 93.33% at a concentration of 90 mg mL-1. The lowest concentration of 30 mg mL-1 resulted in a mortality rate of 46.66% after 96 hours of treatment.Keywords: hard tick; biological control; combination of natural products. Extratos alcoólicos de Vitex agnus-castus e Populus euphratica no controle de Hyalomma anatolicum   RESUMO: O estudo foi realizado desde o início de abril de 2022 até o final de dezembro de 2022 na província de Kirkuk, distrito de Al-Huweija. O estudo examinou a eficácia dos extratos alcoólicos de Vitex agnus-castus e Populus euphratica no controle do carrapato duro Hyalomma anatolicum usando o método de imersão. Todas as larvas tratadas morreram dentro de 48 horas após o tratamento. O extrato alcoólico de P. euphratica foi mais eficaz em matar ninfas de carrapatos na concentração de 90 mg/ml durante a fase ninfal. A taxa de mortalidade foi de 100%. A menor taxa de mortalidade foi de 67,7% na concentração de 30 mg mL-1 após 96 horas de tratamento. Quanto ao extrato alcoólico de V. agnus-castus, a maior taxa de mortalidade na concentração de 90 mg mL-1foi de 93,33%, enquanto a menor foi de 66,66% após 96 horas de tratamento. O extrato alcoólico da combinação atingiu taxa de mortalidade de 93,33% na concentração de 90 mg mL-1. A concentração mais baixa de 30 mg mL-1resultou numa taxa de mortalidade de 46,66% após 96 horas de tratamento.Palavras-chave: carrapato duro; controle biológico; combinação de produtos naturais.